2018
DOI: 10.1108/jmlc-08-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Illicit financial flows: HSBC case study

Abstract: Purpose This paper provides examples of how illicit financial flows (IFFs) are occurring through the formal banking and financial services sector. The purpose of this paper is to explore which elements of anti-money laundering (AML) compliance need to be addressed to strengthen the banking response and reduce the impact of IFFs within the banking sector. Design/methodology/approach The paper uses a number of sources of secondary data including the Swiss leaks data for HSBC and also the Permanent Sub Committee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The governments through the implementation of strong regulation and supervision in financial institutions have denied criminals that want to establish anonymous businesses the opportunity of doing so (Perez et al , 2012; OECD, 2014; Naheem, 2018; Bohoslavsky, 2018). Financial institutions that have strengthened their customer due diligence procedure by profiling and verifying the identities of clients, determining whether a client is a politically exposed person and understanding their sources of wealth have successfully immunised the institution from illicit flows (OECD, 2014; Naheem, 2018; Bohoslavsky, 2018). Governments that are establishing registries of beneficial ownership details on entities, banks have details of true beneficial owners of most accounts in their financial institutions (Cobham, 2014; OECD, 2014; AU/ECA, 2015; Naheem, 2018; Bohoslavsky, 2018; GFI, 2019; Rapanyane and Ngoepe, 2019).…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The governments through the implementation of strong regulation and supervision in financial institutions have denied criminals that want to establish anonymous businesses the opportunity of doing so (Perez et al , 2012; OECD, 2014; Naheem, 2018; Bohoslavsky, 2018). Financial institutions that have strengthened their customer due diligence procedure by profiling and verifying the identities of clients, determining whether a client is a politically exposed person and understanding their sources of wealth have successfully immunised the institution from illicit flows (OECD, 2014; Naheem, 2018; Bohoslavsky, 2018). Governments that are establishing registries of beneficial ownership details on entities, banks have details of true beneficial owners of most accounts in their financial institutions (Cobham, 2014; OECD, 2014; AU/ECA, 2015; Naheem, 2018; Bohoslavsky, 2018; GFI, 2019; Rapanyane and Ngoepe, 2019).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Financial institutions that have strengthened their customer due diligence procedure by profiling and verifying the identities of clients, determining whether a client is a politically exposed person and understanding their sources of wealth have successfully immunised the institution from illicit flows (OECD, 2014; Naheem, 2018; Bohoslavsky, 2018). Governments that are establishing registries of beneficial ownership details on entities, banks have details of true beneficial owners of most accounts in their financial institutions (Cobham, 2014; OECD, 2014; AU/ECA, 2015; Naheem, 2018; Bohoslavsky, 2018; GFI, 2019; Rapanyane and Ngoepe, 2019). This is in line with FATF guideline 24 that is about transparency and beneficial ownership of legal persons, whereas recommendation 25 is about transparency and beneficial ownership of legal arrangements (FATF, 2012/2019).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Mezentceva and Mezentceva (2015) pursued to establish a correlation analysis between the stock market index and financial outflow to measure ML, however, he found it weak. Later, Naheem (2018) found that illicit financial flows may occur through any formal channel in the financial system and it could be more likely in the "securities market". Another study by Muhammad (2014) also gave the general evidence for the effectiveness of AML regulations and discussed the determinants of ML risks which belong to individuals closely related to the banking sector.…”
Section: Existing Studiesmentioning
confidence: 99%
“…In particular, one leading conceptual problem that has dominated the academic literature over a long time refers to the impact of illicit financial flows on the macroeconomic situation. Based on the HSBC Swiss bank's case study, Naheem (2018) demonstrated how banking institutions were connected to illicit financial flow movements through their clients. In this case, financial intermediaries could facilitate different types of illegal financial activities such as money laundering, tax evasion, corruption, bribery, capital flight, and financial resources movement out of economies through illicit financial flows.…”
Section: Literature Reviewmentioning
confidence: 99%